Marketing strategy analysis to improve sales in the hydraulic urban medan group - Muchtar , Yasmin Chairunisa; Inneke Qamariah; Nasution , Inggrita Gusti Sari; Frida Ramadini; Fadli (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Indonesia is an agrarian country which means that agriculture plays an important role in the overall national economy. The agricultural sector is one of the bases that are highly expected in supporting economic growth. The business opportunity from the vegetable business using the hydroponic method is very promising. Especially for fulfilling the food and nutritional needs of the community itself, since very little quality of food intake from vegetables and fruits for the people of Indonesia in particular. Tanjung Morawa area is located on the outskirts of Medan, known as a center for ornamental plants, fruits and vegetables. Communities in this area make crop cultivation a livelihood. This study aims to study strengths, weaknesses, opportunities and threats (SWOT analysis) of the quality of hotel services in the city of Medan in the MICE industry. The research method used is a qualitative method using an internal factor evaluation (IFE) matrix and an external factor evaluation (EFE) matrix with decision making using the Quantitative Strategic Planning Matrix (QSPM) matrix. The results of this study indicate that shows that the development of marketing strategies based on social media. Analysis of external and internal factors using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices indicate that the internal influence is greater than the internal factors.